Selective Laser Sintering 3D Printing of Carvedilol Tablets: Enhancing Dissolution Through Amorphization - Nikola Pešić; Branka Ivković; Tanja Barudžija; Branka Grujić; Svetlana Ibrić; Djordje Medarević (Pharmaceutics)
Background/Objectives: Selective laser sintering (SLS) is one of the most promising 3D printing techniques for pharmaceutical applications as it offers numerous advantages, such as suitability to work with already approved pharmaceutical excipients, the elimination of solvents, and the ability to produce fast-dissolving, porous dosage forms with high drug loading. When the powder mixture is exposed to elevated temperatures during SLS printing, the active ingredients can be converted from the crystalline to the amorphous state, which can be used as a strategy to improve the dissolution rate and bioavailability of poorly soluble drugs. This study investigates the potential application of SLS 3D printing for the fabrication of tablets containing the poorly soluble drug carvedilol with the aim of improving the dissolution rate of the drug by forming an amorphous form through the printing process. Methods: Using SLS 3D printing, eight tablet formulations were produced using two different powder mixtures and four combinations of experimental conditions, followed by physicochemical characterization and dissolution testing. Results: Physicochemical characterization revealed that at least partial amorphization of carvedilol occurred during the printing process. Although variations in process parameters were minimal, higher temperatures in combination with lower laser speeds appeared to facilitate a greater degree of amorphization. Ultimately, the partial conversion to the amorphous form significantly improved the dissolution of carvedilol compared to its pure crystalline form. Conclusions: Obtained results suggest that the SLS 3D printing technique can be effectively used to convert poorly water-soluble drugs to their amorphous state, thereby improving solubility and bioavailability.